Redox Metabolomics of Menthol in Children's Plasma with Second-Hand Cigarette and Electronic Cigarette Exposures - Matthew Ryan Smith; Zachery R. Jarrell; Ken H Liu; Choon-Myung Lee; Edward T Morgan; Young-Mi Go; Dean P. Jones (Advances in Redox Research)
Background: Cigarettes and electronic cigarettes generate many redox-active materials which could impact children's health through second-hand exposures. High-resolution metabolomics methods enable use of non-targeted mass spectrometry of plasma to test for redox consequences of second-hand exposures. Objectives: Our objectives were to test for oxidative stress metabolites and altered metabolic pathways associated with second-hand exposure to redox-active flavorants and flavorant metabolites in plasma of infants and children. Methods: Untargeted plasma metabolomics data for infants and children in a population known to include individuals with second-hand exposures to cigarettes and electronic cigarettes were analyzed for cotinine and metabolites of flavorants. A metabolome-wide association study (MWAS) was performed separately for cotinine and menthol glucuronide, derived from the redox-active flavorant, menthol. Pathway enrichment analysis was used to identify metabolic pathways, and xMWAS was used to detect metabolic communities associated with flavorant metabolites. Results: Menthol glucuronide was one of several flavorant metabolites positively correlated with cotinine. MWAS and pathway enrichment analysis revealed that some pathways associated with both menthol glucuronide and cotinine, while others only associated with menthol glucuronide, including sphingolipid, glycerophospholipid, antioxidant, N-glycan and mitochondrial energy metabolism. 4-hydroxynonenal and other oxidized lipids positively correlated with menthol glucuronide. Discussion: The results show that flavorants from second-hand electronic cigarette and cigarette exposures in infants and children are associated with changes in redox metabolism which are known to associate with human lung diseases.